INVESTIGATIONS ON WATER QUALITY PARAMETERS AND ICTHYOFAUNAL DIVERSITY OF THE RIVER TANGON AT RADHIKAPUR, UTTAR DINAJPUR, WEST BENGAL, INDIA - SARKAR, MANASI; MONDAL, DEBASHRI (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
The physicochemical parameters and ichthyofauna diversity of the water of the internationally important river Tangon at the Radhikapur village in Uttar Dinajpur district of West Bengal were studied for one year from December 2019 to November 2020. The study was done monthly from the four selected sampling sites of the Tangon river. Water temperature varied from 16.80°C to 32.60°C at all the sites during the study. pH ranged from 7.0 to 8.5, indicating the slightly alkaline nature of the water. Higher values of electrical conductivity were observed in the summer months. Free CO2 showed a positive correlation with water temperature and total hardness during the entire study. The lowest value of dissolved oxygen was observed to be 1.80 mgL-1 at Site 1 and Site 2, which might be due to the use of fertilizer at the nearby agricultural field and lifting of excessive sand from the Tangon river. The sudden increase in dissolved oxygen concentrations at all the sites from March to June might be due to the lesser anthropogenic activities during the lockdown in India because of the Covid-19 Pandemic situation. Total hardness (57.40 mgL-1 to 125.00 mgL-1) had a significant negative correlation with transparency at Site 2. Chloride (3.00 mgL-1 to 24.14 mgL-1) had a significant correlation with pH and total hardness at Site 1. BOD was varied between 1.00 mgL-1 and 11.04 mg L-1. The highest BOD was found in December at Site 4, which was much greater than the drinking and bathing water standard set by CPCB. It may be due to the higher level of pollution due to the increasing level of anthropogenic activities. The study on ichthyofauna diversity revealed a total of 40 species of fish belonged to seventeen families from the different sites of the Tangon river during the entire study period. Cyprinidae was found to be the most dominant family throughout the study period. Eight species of fishes were under the vulnerable category (20%) and three species were under a near threatened category (7%). The present study will help formulating the future policy for conservation and proper management of the fish diversity in the Radhikapur village of the Tangon river. Public awareness is very much important for the conservation of the river.